ADVANCING PRECISION - Marcel Ivanov (Romanian Neurosurgery, 2024)
Augmented reality (AR) technology is revolutionizing spine surgery, offering unprecedented intraoperative image guidance and enhancing patient safety, particularly in complex procedures. This presentation explores the expanding applications of AR in spinal surgery, highlighting recent technological advances that have transformed surgical practices. In addition to improving surgical precision and accuracy, AR provides real-time visualization of critical anatomical structures, aiding in navigation and decision-making during intricate spinal procedures.